Cambios fisiológicos de la función tiroidea en el embarazo : bases para la interpretación de las pruebas tiroideas (2013)
ABSTRACT: A proper understanding of thyroid physiology and its changes through pregnancy is critical to suspect diseases affecting the functioning of the hypothalamic-pituitary-thyroid axis, and to make a proper interpretation of the tests that measure its function. Alterations in thyroid function tests are common during pregnancy, and it may be difficult to distinguish them from those due to disease. Clinical hypothyroidism and hyperthyroidism are rare during pregnancy (0.2% to 0.36%), but subclinical forms are more frequent (around 2%). Iodine is essential as substrate for thyroid hormone synthesis, and the requirements vary according to the population and the moment of pregnancy. Infertile couples have five to ten times more thyroid disorders; for that reason they should be studied as to thyroid function when searching for the cause of the infertility. Autoimmunity has been associated with maternal and perinatal complications such as abortion, preterm delivery and postpartum thyroiditis; some studies have shown that their incidence decreases with levothyroxine. This review includes the following aspects: thyroid physiology during pregnancy, thyroid function and fertility, iodine and pregnancy, anti-thyroid antibodies and pregnancy, thyroid function tests during pregnancy, and screening for thyroid disorders in pregnant women.